Comments on Weiner, Resnick and Scientific Debate - Goodman, Jonathan (Education Policy Analysis Archives, 2003)
Lois Weiner (2003) and Lauren Resnick (2003) have advanced substantially different views of the success of the reforms undertaken by Community School District Two (CSD2) in New York city. Weiner's position vis a vis District Two has probably conferred a greater measure of objectivity to her views. Criticisms of scholarly work, even when sharply worded, are neither personal nor unscientific; indeed they are quite common in all the sciences.